Service and Product Quality terhadap Keputusan Customer Membuka Simpanan Umroh di BMT Sunan Drajat Pusat (Studi BMT Sunan Drajat Pusat) - Anisaul Wahdah; Siswadi; Erly juliyani (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2019)
Service and product quality are 2 factors that influence customer decisions. Service components are used to give a good impression to consumers. So that consumers can attract other potential customers. Product quality is also a component of understanding the products offered with more selling value that is not owned by competitors' products. Umrah deposits make it easier for customers to determine the departure of Umrah in a planned manner and help in the management of funds to perform Umrah worship. Research objectives; 1. To find out whether the service affects the decision of customers to open Umrah deposits at BMT Sunan Drajat Pusat. 2. To find out whether the quality of the product affects the decision of customers to open Umrah deposits at BMT Sunan Drajat Pusat. This type of research uses quantitative research methods. The data used is the primary data of secondary funds. The instruments used are questionnaires and documentation. Data analysis techniques use multiple linear regression tests and hypothesis tests. The results of this study 1) service variables affect the decision of customers to open Umrah deposits. This can be seen from the results of multiple regression analysis and hypothesis tests obtained indicators that greatly affect employee service to customers with a Test value of T 3,379 meaning that the service has a positive and significant effect on the decision of customers to open Umrah savings. 2) Product quality variables affect the decision of customers to open Umrah deposits. This can be seen from the results of multiple regression analysis and hypothesis tests obtained indicators that are very influential is the product can be trusted by customers with a test value of T 3,369 meaning the quality of the product has a positive and significant effect on the decision of the customer to open Umrah savings.